2016
DOI: 10.1080/1357650x.2016.1196214
|View full text |Cite
|
Sign up to set email alerts
|

Reading and writing direction effects on the aesthetic appreciation of photographs

Abstract: Does reading and writing direction (RWD) influence the aesthetic appreciation of photography? Pérez González showed that nineteenth-century Iranian and Spanish professional photographers manifest lateral biases linked to RWD in their compositions. The present study aimed to test whether a population sample showed similar biases. Photographs with left-to-right (L-R) and right-to-left (R-L) directionality were selected from Pérez González's collections and presented in both original and mirror-reversed forms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…This would provide a parsimonious explanation of the leftward bias and its emergence in older children who have more reading experience. In addition, habitual left-to-right scanning has been found to influence the aesthetic appreciation of pictures when the directionality of a picture is congruent with scanning direction (Chahboun et al, 2017;Chokron & De Agostini, 2000;Ishii, Okubo, Nicholls, & Imai, 2011). It is possible that the arrangement of an attractive side/unattractive side is more congruent with a left-to-right reading direction than is the reverse arrangement, which enhances perceptual fluency and aesthetic appreciation (see Chahboun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would provide a parsimonious explanation of the leftward bias and its emergence in older children who have more reading experience. In addition, habitual left-to-right scanning has been found to influence the aesthetic appreciation of pictures when the directionality of a picture is congruent with scanning direction (Chahboun et al, 2017;Chokron & De Agostini, 2000;Ishii, Okubo, Nicholls, & Imai, 2011). It is possible that the arrangement of an attractive side/unattractive side is more congruent with a left-to-right reading direction than is the reverse arrangement, which enhances perceptual fluency and aesthetic appreciation (see Chahboun et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance to the current research is the study by Chahboun, Flumini, González, McManus and Santiago (2017) which investigating the effect of reading direction and picture directionality on the aesthetic appreciation of photographs. They found that when reading direction was congruent with the directional arrangement of a photograph it increased aesthetic appreciation, which they suggest might be because greater congruence enhances perceptual fluency (Reber, Schwarz, & Winkielman, 2004) and thereby aesthetic appreciation.…”
Section: Experiments 1 Introductionmentioning
confidence: 99%
“…It is curious that, while many of these studies revolve centrally around the perception of beauty (e.g., Nachson et al, 1999 ; McManus, 2005 ; Masuda et al, 2008 ; De Agostini et al, 2010 ; Powell and Schirillo, 2011 ; Treiman and Allaith, 2013 ; McManus and Stöver, 2014 ; Chahboun et al, 2016 ), very few of them give any concrete definition as to what aesthetic entails. It is possible that this is a conscious choice, in the same way that Weber famously declined to offer a definition of religion in his treatise on the matter ( Weber, 1922 ).…”
Section: Definitions Of Aesthetics In Philosophy and Sciencementioning
confidence: 99%
“…( Christman and Pinger, 1997 ; Nachson et al, 1999 ; Chokron and De Agostini, 2000 ; González, 2012 ; Friedrich et al, 2014 ; Chokron et al, 2016 ). Facing directions in portraits would be another example of this ( Chahboun et al, 2016 ), as well as directionality in bodily composure, such as a subject leaning against a table or chair ( González, 2012 ). Here also would be images of objects with an implied front, such as a triangle ( Christman and Pinger, 1997 ) or objects that indicate a direction, such as a statue with an extended arm ( Christman and Pinger, 1997 ; Chokron and De Agostini, 2000 ).…”
Section: Approaches To Directionality In Researchmentioning
confidence: 99%
“…The effect of spatial biases also emerges in social cognition-for instance, when envisaging social groups in space (Hegarty, Lemieux & McQueen, 2010;Maass, Suitner, Favaretto, & Cignacchi, 2009;Suitner & Maass, 2016). Similarly, aesthetic preferences in artworks (Chahboun, Flumini, Pérez González, McManus, & Santiago, 2017;Friedrich & Elias, 2016;Pérez González, 2012;Suitner & Maass, 2007) or interpretation of soccer games (Maass, Pagani, & Berta, 2007) are affected by script direction. In addition, and more relevant for our research, reading and writing direction has been shown to play a critical role in scanning habits (Afsari, Keshava, Ossandón, & König, 2018;Chokron, Kazandjian, & De Agostini, 2011).…”
mentioning
confidence: 99%